HOBSBAWN, Eric J. Como mudar o mundo: Marx e o marxismo, 1840-2011. São Paulo: Companhia das Letras, 2011. Doi: 10.5212/Emancipacao.v.12i2.0011 - Carvalho, Gabriel Ferreira; Schimanski, Édina (Emancipação, 2013)
Resenha do livro "Como mudar o mundo: Marx e o marxismo, 1840-2011", de Eric Hobsbawn.